Hammarskjold - Urquhart, Brian (New York Knopf, 1994)
As the 1990s place greater demands on the UN, this inspiring biography shows how Hammarskjold perfected the active but quiet diplomacy that proved successful in a series of seemingly hopeless situations, from the Suez Crisis to Indochina, and how he stood up for principle against the greatest powers
Includes bibliographical references
Keywords: Hammarskjöld, Dag, 1905-1961.